Genetic identification and gut content of Gerong Fish Osteochilus waandersii from Larai River - Kemalok, Jai; Zakaria, Mohammad Zulhusni; Azahar, Muhammad Asyraff; Mohamed Rehan, 'Aisyah; Badrulhisham, Nur Sabrina; Kamarudin, Kamarul Rahim (2023)
Gerong fish, or Osteochilus waandersii, is a popular freshwater fish among the Jakun tribe in Kampung Peta, Johor National Park of Endau-Rompin, particularly for its use in traditional medicine to alleviate dizziness by consuming its raw gut. Despite its cultural significance, the genetic and feeding behavior of Gerong fish remains unclear. This study aimed to amplify the mitochondrial DNA barcode region of Gerong fish for genetic identification and to identify its gut content. The DNA barcodes were produced using polymerase chain reaction and single-pass DNA sequencing of partial COI gene, and the gut content was observed using stereo microscope. Several five partial COI gene sequences were successfully obtained after DNA sequencing. In addition, the results of BLAST analysis with percent identities of 96.24% to 97.20% along with the phylogenetic inference of maximum likelihood analyses suggested the Gerong fish as Osteochilus waandersii or the Waanders's hard-lipped barb. The sequences were deposited in GenBank (accession numbers MN223396-MN223400). Microscopic observation of the fish guts revealed undigested worms and digested aquatic mosses, known as lumut batuk. These findings mark a significant step forward in understanding the genetics and feeding behavior of the Gerong fish